Skull Base Reconstruction in the Pediatric Patient - Duek, Irit; Pener-Tessler, Alon; Yanko-Arzi, Ravit; Zaretski, Arik; Abergel, Avraham; Safadi, Ahmad; Fliss, Dan M. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction Pediatric skull base and craniofacial reconstruction presents a unique challenge since the potential benefits of therapy must be balanced against the cumulative impact of multimodality treatment on craniofacial growth, donor-site morbidity, and the potential for serious psychosocial issues.Objectives To suggest an algorithm for skull base reconstruction in children and adolescents after tumor resection.Materials and Methods Comprehensive literature review and summary of our experience.Results We advocate soft-tissue reconstruction as the primary technique, reserving bony flaps for definitive procedures in survivors who have reached skeletal maturity. Free soft-tissue transfer in microvascular technique is the mainstay for reconstruction of large, three-dimensional defects, involving more than one anatomic region of the skull base, as well as defects involving an irradiated field. However, to reduce total operative time, intraoperative blood loss, postoperative hospital stay, and donor-site morbidity, locoregional flaps are better be considered the flap of first choice for skull base reconstruction in children and adolescents, as long as the flap is large enough to cover the defect. Our “workhorse” for dural reconstruction is the double-layer fascia lata. Advances in endoscopic surgery, image guidance, alloplastic grafts, and biomaterials have increased the armamentarium for reconstruction of small and mid-sized defects.Conclusions Skull base reconstruction using locoregional flaps or free flaps may be safely performed in pediatrics. Although the general principles of skull base reconstruction are applicable to nearly all patients, the unique demands of skull base surgery in pediatrics merit special attention. Multidisciplinary care in experienced centers is of utmost importance.
Keywords: skull base surgery; pediatric oncology; microvascular; free tissue reconstruction; endoscopic; skull base reconstruction